PC(sp3)P pincer carbonyl complexes of iridium(i), and iridium(iii)1. Issue 20 (6th March 2015) - Jonasson, Klara J.; Polukeev, Alexey V.; Wendt, Ola F.
<x xml:space="preserve">Abstract</x> The first aliphatic iridium pincer complex with a syn-orientation of the α- and hydride hydrogens is reported and it is shown to be the thermodynamically more stable isomer.